Development of E-module ESD Context Based on Flipped Classroom on Self-Awareness of Junior High School Students - Purnawati, Sri; Suhendar, Suhendar; Ratnasari, Jujun (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Background: Sustainable development has derivatives in the form of Education for Sustainable Development (ESD), one of the supporters of sustainable development. One of the competencies contained in ESD is self-awareness, which needs to be supplied to students. In terms of providing self-awareness to students in the field of Education, there needs to be appropriate media, one of which is e-modules. Method: This study aims to develop an e-module for the context of flipped classroom-based ESD on the self-awareness of junior high school students. The type of research is Research and Development using the development of the ADDIE model, with stages (1) (Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The study subjects were 18 students of grade VIII A SMPN 1 Sukabumi. The instruments used in this study were validation sheets for material experts, media experts, and linguists, pretest and post-test questions, attitude scale sheets, and response sheets to determine the effectiveness of e-modules and self-awareness competencies in students. Results: From the results of this study, an analysis was obtained based on interviews that the e-module of the flipped classroom-based ESD context on the self-awareness of junior high school students so that the development of an e-module with validation results stated that the e-module was included in the very valid category with a percentage of 91.3%, testing the effectiveness of the calculation of the N-Gain value states that the e-module is in the medium category with an average N-Gain of 0.62, the attitude scale sheet states that students have high self-awareness competence, the positive attitude scale is at a percentage of 86.2% which is very good and the response test states that this e-module is suitable for use with a percentage of 93.63% Conclusion: Development of e-module using the ADDIE model is feasible to use for self-awareness in the learning process